Adrenocortical carcinoma: presentation and outcome of a contemporary patient series - Iiro Kostiainen; Liisa Hakaste; Pekka Kejo; Helka Parviainen; Tiina Laine; Eliisa Löyttyniemi; Mirkka Pennanen; Johanna Arola; Caj Haglund; Ilkka Heiskanen; Camilla Schalin-Jäntti (Humana Press Inc., 2022)
Background: Adrenocortical carcinoma (ACC) is a rare endocrine carcinoma with poor 5-year survival rates of < 40%. According to the literature, ACC is rarely an incidental imaging finding. However, presentation, treatment and outcome may differ in modern series.
Design and methods: We studied all patients (n = 47, four children) from a single centre during years 2002–2018. We re-evaluated radiologic and histopathological findings and assessed treatments and outcome. We searched for possible TP53 gene defects and assessed nationwide incidence of ACC.
Results: In adults, incidental radiologic finding led to diagnosis in 79% at median age of 61 years. ENSAT stage I, II, III and IV was 19%, 40%, 19% and 21%, respectively. Nonenhanced CT demonstrated > 20 Hounsfield Units (HU) for all tumours (median 34 (21–45)), median size 92 mm (20–196), Ki67 17% (1–40%), Weiss score 7 (4–9) and Helsinki score 24 (4–48). ACC was more often found in the left than the right adrenal (p < 0.05). One child had Beckwith-Wiedemann and one a TP53 mutation. In adults, the primary tumour was resected in 88 and 79% received adjuvant mitotane therapy. Median hospital stay was significantly shorter in the laparoscopic vs. open surgery group (4 (3–7) vs. 8 (5–38) days, respectively; p < 0.001). In 3/4 patients, prolonged remission of > 5 to > 10 years was achieved after repeated surgery of metastases. Overall 5-year survival was 67%, and 96% vs. 26% for ENSAT stage I–II vs. III–IV (p < 0.0001). ENSAT stage and Ki67 predicted survival, type of surgery did not. Mitotane associated with better survival.
Conclusions: Contemporary ACC predominantly presents as an incidental imaging finding, characterised by HU > 20 on nonenhanced CT but variable tumour size (20–196 mm). Malignancy cannot be ruled out by small tumour size only. The 5-year survival of 96% in ENSAT stage I–III compares favourably to previous studies.